Research methods in language learning - Nunan, David (New York Cambridge University Press, 1992)
The book presents a balanced and objective view of a range of methods including formal experiments, introspective methods (diaries, logs, journals, and stimulated recall), interaction and transcript analysis, ethnography, and case studies. It covers elicitation techniques, program evaluation, and action research. It also emphasizes the practical and professional value to language teachers of initiating their own research.
Includes bibliographical references and index
Keywords: Cơ bản